Novel ecofriendly spectrophotometric methods for the determination of six dihydropyridines calcium channel blockers through derivatization with sulfophtalein dye: application to tablet analysis - Mariana Horyn; Liubomyr Kryskiw; Tetyana Kucher; Nadiya Zarivna; Olha Poliak; Liliya Logoyda (BMC Chemistry)
Abstract Novel, «green» and simple visible spectrophotometric procedures for the determination of six dihydropyridines CCBs (amlodipine besylate (AML), lacidipine (LAC), levamlodipine besylate (LAML), nifedipine (NIF), nimodipine (NIM) and nitrendipine (NIT)) through derivatization with the sulfophthalein dye bromophenol blue (BPB) have been developed. The optimal parameters for CCBs spectrophotometric analysis via complex formation using BPB were as follows: detection wavelength—596 nm, reaction time—5 min, ratio of reacting components—1:1, operating temperature—25 ± 2 °C. The concentration was linearly proportional to absorbance values in the range of 3.40—17.00 μg/mL (AML), 1.14—9.11 μg/mL (LAC), 1.14—9.08 μg/mL (LAML), 4.16—12.40 μg/mL (NIF), 0.84—5.86 μg/mL (NIM), 6.52—19.60 μg/mL (NIT). The developed methods are colorimetric and therefore does not require a UV instrument to quantify these drugs. The proposed approach was more efficient in terms of time reliability, sensitivity and «greenness» than other recorded spectrophotometric methods and can be easily implemented for routine pharmaceutical analysis.